Analisis Penyebab Amblasan Ruas Jalan (Studi Kasus: Ruas Jalan Gunung Ulin – Gunung Sari) - Yusti Yudiawati; Rusdiansyah (Jurnal Serambi Engineering, 2024)
The different behaviour of soils from one region to another requires in-depth identification of the reaction of soils to certain treatments. A comprehensive study is needed to obtain information on the cause and effect of geotechnical cases such as collapse and landslide. The analysis conducted in this paper is based on the collapse of the Gunung Ulin - Gunung Sari road section that occurred in 2018 until the emergence of potential landslides on the excavated slope in 2021 for the construction of retaining walls. The analysis was carried out by reviewing the location of the collapse and conducting identification in the form of field and laboratory soil tests. The information obtained was then used to analyse the stability of the slope under review with the Geo5 application. The results of the analysis based on the geotechnical approach assumed that the collapse was caused by the condition of the soil layer itself in the form of soft clay and claystone whose condition was influenced by high rainfall during the time span of the incident. The analysis results obtained in this paper are expected to be a reference in anticipating similar events to occur in the future.